Blaming others: Individual differences in self-projection. (October 2022) - Kaufmann, Martina; Quirin, Markus; Baumann, Nicola
Abstract: Projection is the tendency to falsely attribute one's own feelings, motives, or intentions onto others. Despite its rich theoretical roots and great value in clinical practice, projection is underexplored in empirical research, which may be partly due to the ongoing challenge of adequately measuring projection. The present research shows that individual differences in the ability to self-regulate emotions (i.e., action versus state orientation) predict projection (i.e., blaming others for one's own mistakes). Specifically, we asked participants to choose from attractive as well as unattractive options and then assessed the extent to which they falsely attribute their own unattractive choices as assigned or recommended by another person. In three studies ( N 1  = 111; N 2  = 68, 79% female; N 3  = 108, 87% female), poor emotion regulators (i.e., state-oriented participants) blamed others for their own unattractive choices under naturally occurring (Studies 1 & 2) and experimentally induced negative affect (Study 3). This tendency towards projection was absent among people with high abilities to self-regulate emotions (i.e., action-oriented participants). Highlights: It does not always apply to everyone. It applies to people who attempted to defend themselves from negative affect. It applies to people with deficits in emotional self-regulation facing negative affect. It applies to people with deficits in emotional self-regulation facing own bad decisions.